Makna Dan Fungsi Tradisi Ngaruat Lembur Bagi Masyarakat Kampung Adat Cibedug Desa Cikole Kecamatan Lembang Kabupaten Bandung Barat - Anisa, Tiya; Poerana, Ana Fitriana; Budhiharti, Tri Widya (Peneliti.net, 2025)
This research discusses the meaning and function of ngaruat lembur culture in the Cibedug Traditional Village community, Cikole Village, Lembang District, West Bandung Regency. Ngaruat Lembur cultural tradition aims to express gratitude and thanks to God who has given everything to the people of Kampung Adat Cibedug. The community also believes that by carrying out this tradition they can avoid all dangers. The purpose of this research is to find out communicative events in communication components contained in Ngaruat Lembur culture such as Setting/Scene, Participants, Ends. The ethnographic model of communication SPEAKING (Setting/Scene, Participants, Ends) is used as a method in this research and symbolic interaction theory complements this research. The type of research used is qualitative, the informants in this study are peni sepuh, elders, chairman of the Ngaruat Lembur organizing committee, the community and the head of Cikole Village. Data collection techniques using observation, interviews and documentation. The conclusion of this research is that communication components such as: Setting/Scene, Participants, Ends, are elements that form communicative events in the Ngaruat Lembur cultural tradition.